Biogeography of bats in Iran: Mapping and disentangling environmental and historical drivers of bat richness. (18th November 2021) - Kafash, Anooshe; Ashrafi, Sohrab; Yousefi, Masoud
Abstract: Bats are facing several threats like land‐use change, habitat loss, overexploitation for food, mortality at wind energy turbine installations, disease, and climate change worldwide. Defining biodiversity of bat species can help conservation biologists to prioritize areas for bat conservation. In this study, we assembled distribution records of all bats of Iran to generate the first richness map of bats, as no richness map is available for bat species in the country. By constructing generalized linear models, we determined which historical and environmental factors drive the richness of bat species across the country. Results of richness mapping showed that Zagros Mountains host the highest number of species in Iran. We found that precipitation is the most influential variable in shaping bat richness in Iran by explaining 26% of variation in species richness. Topographic heterogeneity, with 19% of explained variance, was the second most important determinant of bat richness. We also estimated bat assemblage similarity among the biomes in the country. Temperate Grasslands, Savannas, and Shrublands biome was the most distinct biome based on bat assemblage. On the other hand, Montane Grasslands and Shrublands and Deserts and Xeric Shrublands were the most similar biomes based upon distributions of the bat species. Areas that were identified to have higher species diversity were regions with high priority for the conservation of bat biodiversity in the country. Temperate Grasslands, Savannas, and Shrublands, which host the most unique assemblage of bat species, have high importance for conservation. Therefore, to enhance the conservation of bats and maintain the important ecosystem services which they provide, we must have a clear knowledge of their richness and essential needs. Abstract : In this study, we generated the first richness map of bats of Iran. We showed that Zagros Mountains host the highest number of bat species in Iran. Precipitation and topographic heterogeneity were the most influential variable in shaping bat richness in the country. We found that maximum number of bat species occur in Temperate Broadleaf and Mixed Forests and Deserts and Xeric Shrublands biomes with 37 and 33 species respectively.